Bayesian Estimation of Exponentiated Inverse Rayleigh Distribution - Kumar Rao, Arun; Pandey , Himanshu (International Journal of Scientific Research and Management (IJSRM), 2021)
In this paper, exponentiated inverse Rayleigh distribution is considered for Bayesian analysis. The expressions for Bayes estimators of the parameter have been derived under squared error, precautionary, entropy, K-loss, and Al-Bayyati’s loss functions by using quasi and gamma priors.